MODEL EXAMPLE NON EXAMPLE TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Larasati, Annisa Dewi; Madyawati, Lilis; Subekti, Tabah; Subekti, Tabah (Universitas Muhammadiyah Magelang, 2015)
This research aims to determine the effect of the example non example models of learning achievement in Social science Students of State Elementary School Grade 1 Maduretno Kaliangkrik Magelang. The approach used in this study the pre-experimental research, design The One Group Pretest-Posttest Design, by 9 meetings, are given treatment through learning in the classroom. The subjects of this study were 15 students who have learning achievement of Social Sciences is low. The sampling technique used is saturated sampling technique. There are two variables used in the research are: the dependent variable in the form of learning achievement of Social Sciences, as well as the independent variable in the form of a model example of non example. The data collection technique used is the learning achievement test Social Sciences.The results of a study reported an average score early measurement of learning achievement of Social Sciences students is 56.80, while the average score of the final measurement of learning achievement of Social Sciences students are reaching 77,87.Hypothesis testing using analytical techniques Wilcoxon signed rank test with SPSS for windows version 22.00. Based on the analysis of achievement learn there is a difference of Social Sciences students between the initial measurement and the final measurement with the value of Z at -3415 with sig 0,000 (sig <0.05), which means that there is a model example of non example influence the learning achievement of Social Sciences.